Exploring the Influence of Emotional Autonomy on Academic Flow Theory: A Study on Cadets at Politeknik Ilmu Pelayaran (PIP) Makassar - Syam, Makmur (PT. Riset Press International, 2023)
Emotional autonomy is the ability of young cadets to act independently, take the initiative, overcome obstacles, and effectively manage emotions while engaging in activities. Academic flow is a state experienced by individuals when fully immersed, focused, concentrated, comfortable, and enjoying what they do due to intrinsic motivation. This study examines the relationship between Emotional Autonomy and academic flow theory among cadets at Politeknik Ilmu Pelayaran (PIP) Makassar. The sample consisted of 170 participants selected through random sampling. The quantitative research method used the emotional autonomy scale and the LIS Inventory Flow Academic as measurement tools. Data analysis was conducted using the Product Moment correlation technique with SPSS 24.0 for Windows. The results revealed a correlation coefficient of 0.643 between emotional autonomy and academic flow, with a significance level 0.000 (p<0.01). The findings indicate a positive relationship between emotional autonomy and academic flow. This research provides valuable insights for Cadets in enhancing their emotional autonomy to attain a state of academic flow during lectures and residential activities.